The Effect of Net Interest Margin as a Mediator and Selected Factors in Determining the Profitability of Digital Banks - Muhammad Raditya Rahagi; Najmudin Najmudin; Rio Dhani Laksana (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Most digital banking companies experience negative returns on assets so it is necessary to analyze the factors change its financial position. This research intends to investigate the magnitude of loan to deposit, non-performing loan, and capital adequacy on profitability using net interest margin as mediation. In this research, the contents of sample are 7 (seven) digital banks registered at IDX during the period 2019 to the third quarter of 2022. The existing data were analyzed using Partial Least Square. As the result, the findings show that the magnitude of loan to deposit has a positive effect on net interest margin and then on profitability. Furthermore, net interest margin could to mediate significantly the impact of loan to deposit towards profitability. Meanwhile, non-performing loan has no beneficial impact to profitability. In addition, capital adequacy has an impact negatively on profitability.